2009
DOI: 10.1136/thx.2009.114439
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation factors in the airways in moderate and severe asthma and the effect of inhaled steroids

Abstract: Background: There is evidence of activation of the extrinsic coagulation cascade in the asthmatic airway, and both plasma and locally derived factors may be involved. The hypothesis that the normal haemostatic balance of healthy airways sampled by sputum induction favours fibrin formation in asthmatic airways, and that inhaled corticosteroids (ICS) and plasma exudation influence this balance, was tested. Methods: ELISA and activity assays were used to measure a 2 -macroglobulin (an index of plasma leakage) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 55 publications
3
71
0
1
Order By: Relevance
“…The regulation of t-PA gene expression is not well described. t-PA is produced by a number of airway cells, including mast cells, macrophages, fibroblasts, endothelial cells, glandular cells, and epithelial cells (38,39). Our immunohistochemistry data demonstrated that t-PA staining was most prominently Figure 7.…”
Section: Discussionmentioning
confidence: 79%
“…The regulation of t-PA gene expression is not well described. t-PA is produced by a number of airway cells, including mast cells, macrophages, fibroblasts, endothelial cells, glandular cells, and epithelial cells (38,39). Our immunohistochemistry data demonstrated that t-PA staining was most prominently Figure 7.…”
Section: Discussionmentioning
confidence: 79%
“…This has been observed in animal models, in the lung tissue of humans with acute lung injury [28] and in patients with pneumonia [29]. Also, there is evidence of activation of the extrinsic coagulation cascade in the asthmatic airway, with involvement of both plasma and locally derived factors [7,8]. This is supported by a recent finding showing local vascular inflammation in asthma and COPD [30], as well as the observation of a higher incidence of PE than DVT in COPD patients [22], and evidence that in other chronic inflammatory disorders, such as diabetes, rheumatoid arthritis and ulcerative colitis, a higher incidence of PE has not been observed [3][4][5].…”
Section: Discussionmentioning
confidence: 88%
“…This has been shown for inflammatory bowel disease [3], rheumatoid arthritis [4], diabetes mellitus [5] and chronic obstructive pulmonary disease (COPD) [6]. Asthma has also been associated with a procoagulant and antifibrinolytic activity in the airways [7,8]. However, whether this procoagulant shift translates into a higher risk of symptomatic VTE is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Although coagulation is classically thought to happen in blood vessels, coagulation also occurs on the luminal surface of the airway epithelium (14). Compared with control subjects, coagulation activity and the concentrations of coagulation-associated mediators, including thrombin, thrombin-antithrombin complex, and tissue factor (TF) are elevated in sputum and bronchoalveolar lavage (BAL) fluid from patients with asthma (15)(16)(17). TF is a 47-kD transmembrane protein that functions as the primary cellular initiator of blood coagulation by binding Factor VII/Factor VIIa (FVII/FVIIa) (18,19).…”
mentioning
confidence: 99%